Conjunctive p16INK4a Testing Significantly Increases Accuracy in Diagnosing High-Grade Cervical Intraepithelial Neoplasia - Bergeron, Christine; Ordi, Jaume; Schmidt, Dietmar; Trunk, Marcus J.; Keller, Thomas; Ridder, Ruediger (American journal of clinical pathology, 2010)
The histopathologic interpretation of cervical intraepithelial neoplasia (CIN) is subject to a high level of interobserver variability and a substantial number of false-positive and false-negative results. We assessed the impact of the conjunctive interpretation of p16INK4a-immunostained slides on the accuracy of community-based pathologists in diagnosing high-grade cervical intraepithelial neoplasia (CIN; CIN 2 and CIN 3) in biopsy specimens. Twelve pathologists rendered independent diagnoses on a set of 500 H&E-stained cervical punch and conization specimens. Results were compared with a dichotomized “gold standard” established by consensus of 3 gynecopathology experts. When p16INK4a-immunostained slides were added and conjunctively interpreted with the H&E-stained slides, a significant increase in diagnostic accuracy for the detection of high-grade CIN was observed (P = .0004). Sensitivity for high-grade CIN was increased by 13%, cutting the rate of false-negative results in half. Agreement of community-based pathologists in diagnosing high-grade CIN was significantly improved (mean κ values advanced from 0.566 to 0.749; P < .0001). Reproducibility of p16INK4a stain interpretation was excellent (κ = 0.899). Our results show that conjunctive interpretation of p16INK4a-stained slides could significantly improve the routine interpretation of cervical histopathology.